Just fracking: a distributive environmental justice analysis of unconventional gas development in Pennsylvania, USA. (15th February 2016) - Clough, Emily; Bell, Derek
Abstract: This letter presents a distributive environmental justice analysis of unconventional gas development in the area of Pennsylvania lying over the Marcellus Shale, the largest shale gas formation in play in the United States. The extraction of shale gas using unconventional wells, which are hydraulically fractured (fracking), has increased dramatically since 2005. As the number of wells has grown, so have concerns about the potential public health effects on nearby communities. These concerns make shale gas development an environmental justice issue. This letter examines whether the hazards associated with proximity to wells and the economic benefits of shale gas production are fairly distributed. We distinguish two types of distributive environmental justice: traditional and benefit sharing . We ask the traditional question: are there a disproportionate number of minority or low-income residents in areas near to unconventional wells in Pennsylvania? However, we extend this analysis in two ways: we examine income distribution and level of education; and we compare before and after shale gas development. This contributes to discussions of benefit sharing by showing how the income distribution of the population has changed. We use a binary dasymetric technique to remap the data from the 2000 US Census and the 2009–2013 American Communities Survey and combine that data with a buffer containment analysis of unconventional wells to compare the characteristics of the population living nearer to unconventional wells with those further away before and after shale gas development. Our analysis indicates that there is no evidence of traditional distributive environmental injustice: there is not a disproportionate number of minority or low-income residents in areas near to unconventional wells. However, our analysis is consistent with the claim that there is benefit sharing distributive environmental injustice: the income distribution of the population nearer to shale gas wells has not been transformed since shale gas development.